Halogen-free imidazolium based ionic liquids for organic and inorganic synthesis - Arco, Susan D. (2011)
Ionic liquids (IL) are designer solvents exhibiting negligible vapor pressure, high thermal stability, wide liquid range, and excellent ability to dissolve various inorganic and organic compounds. Typical ILs consist of N,N'-dialkylimidazolium cations and a wide variety of halide-based anions but the presence of halides in these ILs raise environmental concerns when the hydrolysis stability of the anion is poor or when a thermal treatment of the IL in use is necessary. In response to this, two series of halogen-free, 1-alkyl-3-methylimidazolium [RMIM] based ILs, [RMIM] Acetate and novel [RMIM] Lauryl sulfate (LS), have both been prepared through a two step procedure: step (1) involves a reaction between 1-methylimidazole and the appropriate alkylbromide to yield [RMIM] Br with sodium acetate or sodium LS to afford the halogen-free ILs. A comparison of optical properties 1-butyl-3-methylimidazolium [BMIM]LS and [BMIM]Br shows that the interesting excitation wavelength-dependent behavior observed in both ILs is typical of ILs bering the imidazole moiety. The Diels-Alder reaction provides a means by which heterocyclic rings may be produced from acyclic precursors in a single step and endoselectivity (endo:exo=91:1) and product yield (89%) obtained for the Diels-Alder reaction between cyclopentadiene and methyl acrylate ina 1-hexyl-3methylimidazolium [HMIM]Acetate is remarkably high. The control of the morphogenesis of gold nanoparticles leads to unique properties that are essential to applications such as catalysis and analytical sensing. [RMIM]LS has been utilized both as a solvent and as a stabilizing agent of anisotropic gold nanostructures and the morphogenesis of these gold nanostructures has been examined. Presence of [BMIM]LS stabilized the formation of Au nanoplates as well as intertwined Au nanoparticles and nanorods.
Keywords: Stabilizing agents